Entry and exit in the ICT sector: New markets, new industrial dynamics? - Heli Koski; Carolina Sierimo (The Research Institute of the Finnish Economy (ETLA), 2003)
Network industries have special characteristics that may influence the nature and the order of magnitude of entry and exit barriers in these industries. Consequently, the entry and exit dynamics of network industries such as the information and communications (ICT) sector may differ from those of the traditional industrial sectors. We use data from the Finnish industrial sectors from 1995 to 2000 to empirically explore this question. Our data suggests that, indeed, factors determining the rates of entry and exit are different among ICT and non-ICT industries. The data support our hypothesis that the special characteristics of network industries intensify the role of market concentration and economies of scale as a barrier to entry and exit. This empirical finding emphasizes the importance of antitrust regulation and careful evaluation of potential anti-competitive consequences of mergers and acquisitions in network industries. – entry ; exit ; network industries ; ICT
Keywords: 330; Markteintritt; Informationstechnik; Informationstechnik; Finnland; Marktaustritt